2014
DOI: 10.1016/j.nedt.2013.08.018
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of drinking patterns, prelicensure nursing education, and professional identity formation

Abstract: This collection is found at IUScholarWorks: http://hdl.handle.net/2022/16829 When in the collection and within a category, click on "title" to see all items in alphabetical order. The CollectionThis document is part of a collection that serves two purposes. First, it is a digital archive for a sampling of unpublished documents, presentations, questionnaires and limited publications resulting from over forty years of research. Second, it is a public archive for data on college student drinking patterns on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Nurses, regardless of their roles in the health care system, are called upon to be leaders and advocates who have a moral responsibility to promote the health and safety of all people (17), but traditional methods in pre-licensure education have not always led to the development of strong leaders (3,21). Others have used service learning as an effective strategy to cultivate leadership in pre-licensure students (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses, regardless of their roles in the health care system, are called upon to be leaders and advocates who have a moral responsibility to promote the health and safety of all people (17), but traditional methods in pre-licensure education have not always led to the development of strong leaders (3,21). Others have used service learning as an effective strategy to cultivate leadership in pre-licensure students (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 1 in 5 college females between the ages of 18 and 25 experiences an attempted or completed sexual assault and more than 599,000 college students between the ages of 18 and 24 are injured annually from an alcohol-related incident (1,2). Nursing students themselves are very likely to engage in behaviors that put them at risk for alcohol-related injuries (3,4).Therefore, it is likely that nursing students will encounter campus situations where other students need assistance.…”
Section: Introductionmentioning
confidence: 99%
“…of .86. 8 On the basis of NIAAA definition of high-risk drinking as more than 7 drinks a week for women, we classified students as abstainers, low-risk drinkers, or high-risk drinkers. 2 The university's institutional review board granted approval to conduct this study.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 The research suggests that high-risk drinking and problem behaviors that endanger others may begin in prelicensure education. [7][8][9] Nursing students are taught that they have an ethical responsibility to protect patients from injury that might result from impaired practice, but 1 study found that 4% of the nursing students engaged in patient care while under the influence. 5,6 Another study found approximately 10% of the nursing students endangered others within the previous year by driving when they knew that they had too much to drink.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation